Fungal keratitis: An overview of clinical and laboratory aspects. Issue 12 (27th July 2018) - Mahmoudi, Shahram; Masoomi, Ahmad; Ahmadikia, Kazem; Tabatabaei, Seyed Ali; Soleimani, Mohammad; Rezaie, Sassan; Ghahvechian, Hossein; Banafsheafshan, Ali
Summary: Mycotic keratitis or keratomycosis is a fungal infection with global distribution. The dominant aetiology of this disease varies based on geographical origin, socioeconomic status, and climatic condition. Generally, Aspergillus spp. and Fusarium spp. are common in tropical and subtropical regions and Candida spp. are dominant in temperate areas. Demonstration of fungal elements in microscopic examination besides the isolation of fungi in culture is the gold standard of laboratory diagnosis. As the culture is a time‐consuming procedure, other approaches such as in vivo confocal microscopy which produces real‐time imaging of corneal tissue and molecular techniques have been developed to facilitate rapid diagnosis of fungal keratitis. The first choice of treatment is topical natamycin, although topical amphotericin B is the best choice for Aspergillus and Candida keratitis. Regarding the diversity of fungal aetiology and the emergence of drug resistance in some genera and species, proper identification using molecular methods and antifungal susceptibility testing could provide useful data. Furthermore, as the better efficacy of combination therapy in comparison to monotherapy is reported, in vitro determination of interactions between various drugs seem informative. This review aims to provide a general and updated view on the aetiology, risk factors, epidemiology, clinical and laboratory diagnosis, and management of fungal keratitis.